Channel Tortuosity of Long Laboratory Sparks - Amarasinghe, D.; Sonnadara, D.U.J.; Berg, M.; Cooray, V. (My University, 2007)
Channel tortuosity of 50 cm long laboratory sparks were measured by analyzing a set of images taken by three cameras. The cameras were placed at a radial distance of 200 cm from the spark gap. The angle between any two cameras was 120. The sparks were generated between a steel rod and a plane electrode. The distribution of the direction change of the channel was found to be Gaussian with a standard deviation of 15.3. The average tortuosity of the channel defined as the mean absolute value of the direction change was 11.8  1.4 which is smaller than the average tortuosity of natural lightning and close to the tortuosity of triggered lightning. The average tortuosity is dependent on the segment length used in calculating the direction change. A gradual increase in the average tortuosity (0.08 per cm) was seen when the sparks propagate towards the plane electrode
Keywords: Channel Tortuosity; Laboratory Sparks